ダイ 34 ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1993 - 高尾, 俊則; タカオ, トシノリ; 小池, 仁治; コイケ, ジンジ; 鎌田, 吉博; カマタ, ヨシヒロ; 杉田, 興正; スギタ, オキマサ; 櫻井, 敬三; サクライ, ケイゾウ; Takao, Toshinori; Koike, Jinji; et al. (1996)
P(論文) この報告は第34次南極地域観測隊気象部門が, 1993年2月1日から1994年1月31日まで昭和基地において行った気象観測結果をまとめたものである。観測方法, 設備, 結果の取り扱い等は, 第33次観測隊とほぼ同じである。越冬期間中特記される現象として, 以下のものがあげられる。1)地上気象観測結果によると, 平年に比べ気圧及び気温が著しく低い1年であった。2)合計34回のブリザードがあった。なかでも12月には記録的な強風のA級ブリザードが来襲した。3)最近数年の傾向と同様に, 春期成層圏の著しい低温現象がみられた。成層圏では冬期の低温も顕著であった。4)オゾン全量観測の結果, 過去最大規模のオゾンホールが観測された。全量値は10月11日には140m atm-cmと過去最低値を記録した。5)ブリューワ分光光度計によって, 初めて1年を通じた波長別紫外域日射観測を行った。 This paper describes the results of meteorological observations carried out by the Meteorological Observation Team of the 34th Japanese Antarctic Research Expedition (JARE-34) from 1 February 1993 to 31 January 1994 at Syowa Station. The method of observations, instruments, and statistics at Syowa Station were the same as those of the JARE-33 team. The principal characteristics in the period of JARE-34 are as follows : 1) Annual mean surface air pressure and temperature were somewhat lower than normal. 2) Blizzards were encountered 34 times. There was a record strong blizzard in December. 3) In the stratosphere, air temperature was very low in winter and spring. 4) The deepest ozone hole to date was observed. Total ozone recorded 140m atm-cm on 11th October, the lowest ever at Syowa Station. 5) With the Brewer spectrophotometer, solar spectral UV irradiance was observed through the whole year. departmental bulletin paper